The Trauma of Victimization and the Role of Forgiveness in Mitigating such Feelings - Columbus, Ogbujah (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2013)
In the present world, there are rampant acts of violence, hatred and crime which have left a long trail of victims. Victims of crimes and ‘acts of God’ are traumatized not just by physical injuries but much more by the psychological torture of self-blame and un-forgiveness. To initiate a process of healing, the offender must seek for forgiveness; the victim must forgive as a means of liberating the offender and himself, and the process must entail a structure of restitution, for to forgive without requiring the other to change is not only self-destructive, but ensures that a dysfunctional relationship remains. Hence, a liberating forgiveness, even though it is growing in the act of not holding things over people, must be executed in such a manner that it neither approves, nor excuses the offense as to give the offender the leverage to perpetrate his crime.